Parametric Study of Behavior of Sub-soil of Chitwan District (OCEM Journal of Management, Technology & Social Sciences, 2025)
The “Parametric Study of Behavior of Subsoil of Chitwan District” investigates the geotechnical characteristics of two locations, Mangalpur and Ratnanagar having clayey and sandy soil respectively. This study explores the influence of varying soil parameters, specifically cohesion, water table depth, internal angle of friction and Poisson ratio, on the behavior of foundations in these regions. The investigated data is taken for the analysis which is considered as secondary data. The findings reveal substantial disparities in soil parameters between two location, leading to notable differences in foundation performance. Additionally, the study highlights the significance of foundation width as a critical factor in ensuring stability and minimizing settlement under varying subsoil conditions. A numerical model is developed using PLAXIS 2D. Finite element analysis is carried out using Mohr-coulomb failure criteria to represent two-dimensional soil model. Foundation is modelled and load of 2250 kN/m2 is applied till the soil model fails. Results were presented in charts to visually compare the different parameters between Mangalpur and Ratnanagar using PLAXIS. In 2D finite element analyses, the footing for various widths was modeled and the deformation at cross-section of -1 m depth is discussed. Greater subsoil strength in clay soil is indicated by a higher cohesion value. A lower Poisson’s ratio provides suitable strength for both soils, and the results showed that changing the depth of the water table for both soils suggested that a greater depth enhances subsoil strength in the case of clay, while a smaller depth is advantageous in the case of sand.